The Pine Branch, October 1922 - (:unkn) unknown (Valdosta, Ga. : Writers Club of the Georgia State Womans College., 1922)
The Pine Branch, October 1922. Periodical magazine. Created and published by the Writers Club of the Georgia State Womans College, Valdosta, Georgia, 1922. Includes: editorials, poems, short stories, and other writings. This is the first issue published after South Georgia State Normal College changed to the Georgia State Womans College. **Note**: Volume 6 skipped by Pine Branch staff.
Two Sonnets to the Georgia State Womans College Page 1 | The Story Teller Page 2 | Solemn Reflections of a Sophomore Page 6 | An Intercepted Letter Page 7 | Editorial Page 10 | Y. W. C. A. Page 11 | Locals Page 13 | Alumnae Notes Page 15 | Society Notes Page 16 | Humorous Page 17 |
Keywords: College publications; College student newspapers and periodicals; Valdosta State University--Periodicals; Women; Women's colleges--Georgia--Valdosta; Georgia State Womans College; Valdosta; Schools--Georgia; Education